Novel magnetoliposomes containing magnetic nanoparticles covered with gold as nanocarriers for new antitumor tricyclic lactones - Rio, Irina S. R. (2019)
In this work, core/shell magnetic nanoparticles of manganese ferrite/gold were prepared and characterized. In order to develop applications in combined cancer therapy, the prepared nanoparticles were covered with a lipid bilayer (forming magnetoliposomes), these systems being able to transport drugs. TEM and DLS measurements indicated that these systems exhibit sizes around 120 nm. Two new potential antitumor tricyclic lactones were successfully encapsulated in these nanocarriers. The heating capabilities of the developed nanosystems were evaluated upon excitation with a light source. These multifunctional nanosystems have shown promising results for application combined cancer therapy (chemo/phototherapy).